Tidelaget och hotet mot maskuliniteten ⁠— ett genmäle - Liliequist, Jonas (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1993)
Inger Lövkrona is right in criticizing me for having neglected the cultural construction of male sexuality in my dissertation on the crime of bestiality in 17th- and 18th-century Sweden. However, Lövkrona is incorrect in claiming that it was chiefly younger men who were brought before the courts on this charge. Youths between the ages of fifteen and nineteen comprised by far largest group of accused, which may have been a reflection of actual conditions, while the low percentage of boys in most likely a serious underestimation of actual activity. There is no evidence of any double morality which protected mature men from being accused. Instead, the act of bestiality should be related to a youthful and experimental sexuality whose most significant prerequisite was proximity to domestic animals. Lövkrona wishes to find a connection between the cultural origins of the act of bestiality with maturity and the reigning male ideal. According to Lövkrona, bestiality was a way for grown men to confirm their masculinity. However, there is no evidence that the act of bestiality was a source of male prestige. Quite the contrary; aside from arousing feelings of shock, abhorrence and disgust, the main reaction of the community was ridicule. My interpretation implies that this ridicule had its origins in the fact that the act of bestiality was intimately associated with little boys. The basis for this attitude was the perception of clearing out the stables as children’s work, along with the absence of a male shepherding culture in Sweden with which the act could be identified. When youths or young men performed chores or acts which were associated with little boys, it raised doubts about their masculinity, as when they took over female chores or sexual roles. In this case, the threat towards masculinity came not from "feminization", but from association with pre-pubertal boys. This threat was further underlines by the nature of youth as a period of transition and experimentation featuring recurrent tests of manhood and struggles for prestige. In this struggle, shows of physical strength and success with mild maids was what mattered. Bestiality was something for immature boys and the losers in the competition for girls. In early modern Sweden, this was a significant factor in the cultural construction of the act of bestiality.